HAPPY TREE FRIENDS: Analysis of Violent Content in the Cartoon Series - Arifah, Arifah; Ashidiq, Abdul Rahman; Wismadi, Muhammad Tsaqif (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Happy Tree Friends is one of cartoon series was created by America. This film is a comedy genre, which is deliberately made for children with funny and interesting characters. This film has been watched by hundreds of thousands of viewers both on television and on YouTube. However, this cartoon film with cute characters is not suitable to be shown to children because it visualizes very tragic scenes of violence and death. So, the aim of this research is to find out the frequency and tendency of violent scenes shown in the cartoon film Happy Tree Friends. This type of research is quantitative descriptive. The method used is content analysis. The results of the research after conducting reliability tests based on predetermined categorization stated that 99% of the Happy Tree Friends cartoon films contained scenes of physical violence.